(untitled) (Medical Forum Monthly, 2022)
Objective: To evaluate the bone mineral density in patients of malignant prostate cancer with and without use of androgen deprivation therapy. Study Design: Case control study Place and Duration of Study: This study was conducted at the Urology department of Nishtar Hospital, Multan from April 2021 to March 2022. Materials and Methods: A total of 50 patients with malignant prostate cancer were enrolled in study. Patients were categorized on basis of their use of ADT (case or control). Bone mineral density of patients was measured by using bone densitometry. SPSS version 24 was used for data entry and analysis. P value ≥0.05 was considered as significant. Results: The parameters of bone mineral density (BMD) in ADT and controls patients were almost equal and no statistically significant difference was found, (p>0.050). It was seen that 32.0% patients had normal BMD, 44.0% had osteopenia and 24.0% osteoporosis in ADT patients. Whereas, 36.0% patients had normal BMD, 44.0% had osteopenia and 20.0% osteoporosis in control patients, (p=0.928). Conclusion: Men with prostate cancer in older age have significant bone loss, start of androgen deprivation therapy can cause more decrease in bone mineral density (BMD). Patients on treatment of ADT should have baseline bone mineral densitometry and checked periodically for assessment of possible osteoporosis and fracture risk. Use of bisphosphonate is much costly that cannot be started blindly until recommendations are proven.